EFEKTIVITAS MEDIASI BERDASARKAN PERMA NO. 1 TAHUN 2008 SEBAGAI SARANA PENYELESAIAN SENGKETA DI PENGADILAN DALAM SEMUA TINGKAT PERADILAN - , I Gusti Agung Sumanata, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research is meant to reveal deeper the effectiveness of using mediation in the court as well as elaborating the effectiveness of Supreme Court Regulation No.1 Year 2008 on procedure of mediation in court to mediate the parties in civil cases. The research also explaining procedural law applied in settling the dispute in the court to reach the amicable settlement based on judicial Indonesian system. The research was conducted in the district court of Kebumen, district court of Bogor, and The Supreme Court of Republic of Indonesia. Those mentioned institution have the power and authority to handle dispute on the civil cases connected to mediation. The research type is normative law and done qualitatively. Normative law approach is based on existing law norms. Qualitative research purposes to analyze the data that had been collected, obtained through library and interview. The focus of this research is library research. It means secondary data is the more important than primary data. The research concludes that